Clinical Characteristics and Influencing Factors of Postoperative Pain in Patients Undergoing Gastric Endoscopic Submucosal Dissection - Fen Deng; Liru Pan; Lei Tao; Xiaoyu Qiu; Bing Li; Jing Hao; Huihui Li; Zhenzhen Zhang; Weiwei Ding; Yingying Wang; Bo Ning (Health Care Science)
ABSTRACT Background To comprehensively analyze the clinical characteristics of patients who underwent gastric endoscopic submucosal dissection (ESD) and explore the incidence and influencing factors of postoperative pain. Methods The clinical data of patients who underwent gastric ESD at our center from 2009 to 2024 were retrospectively analyzed. Pain severity was assessed using a visual analogue scale, with a score ≥ 4 defined as postoperative pain. Based on the presence or absence of postoperative pain, patients were divided into a pain group and a control group. Independent factors influencing postoperative pain were identified using multivariate logistic regression analysis. To control for confounding bias, patients in the case and control groups were matched by sex and lesion size, and the matched participants were further analyzed using a conditional logistic regression model. Results In total, 993 patients were analyzed. The incidence of postoperative pain was 9.1% (95% confidence interval [CI], 7.3–11.1). In the univariate analysis, sex, operation duration, anesthesia method, intraoperative electrocoagulation, nasogastric tube placement, and postoperative vomiting were significantly associated with postoperative pain. Multivariate analysis identified eight independent factors: male sex (odds ratio [OR], 0.61; 95% CI, 0.37–0.97; p = 0.04), operation duration (OR, 1.29; 95% CI, 1.03–1.63; p = 0.02), protuberant lesions (OR, 0.43; 95% CI, 0.26–0.71; p < 0.01), antral lesions (OR, 1.84; 95% CI, 1.10–3.05; p = 0.01), intubation general anesthesia (OR, 0.40; 95% CI, 0.22–0.72; p = 0.002), intraoperative electrocoagulation (OR, 0.32; 95% CI, 0.19–0.55; p < 0.01), nasogastric tube placement (OR, 2.005; 95% CI, 1.12–3.57; p = 0.01), and postoperative vomiting (OR, 3.24; 95% CI, 1.40–7.47; p = 0.005). Conditional logistic regression analysis further identified diabetes mellitus (OR, 2.50; 95% CI, 1.03–6.06; p = 0.04). Conclusion Female sex, diabetes mellitus, concave‐type lesions, lesions in the gastric antrum, non‐intubation general anesthesia, absence of intraoperative electrocoagulation, prolonged operation duration, nasogastric tube placement, and postoperative vomiting were independent factors associated with moderate to severe pain after gastric ESD. For patients at increased risk of postoperative pain, appropriate prophylactic and therapeutic measures during the perioperative period may effectively alleviate pain following gastric ESD.